Breaking Barriers : Women’s Ventures In The Digital Realm A Systematic Literature Review - Nuraini, Abdullah; Nur Tasnem, Jaafar; Nuradibah, Mokhtar; Noorazeela, Zainol Abidin; Nadhratul Ain, Ibrahim (Universiti Malaysia Kelantan (UMK), 2025)
In the rapidly evolving landscape of digital platforms, the rise of women entrepreneurs has become increasingly prominent. Despite traditional barriers, more women enter digital entrepreneurship seeking flexibility and income contribution. However, challenges such as limited resources and societal norms persist. This paper presents a systematic literature review exploring the challenges, opportunities and dynamics of women's ventures in the digital realm. The study utilized a systematic literature review of research published between 2017-2024, sourced from Scopus and Web of Science databases. Thematic analysis is applied to classify findings into reasons and challenges driving female participation in digital entrepreneurship. The review identifies digital platforms as crucial for offering women flexibility and market accessibility, essential for managing work and family commitments. However, gender disparities, family responsibilities and limited access to resources remain significant barriers. This study contributes a comprehensive synthesis of existing literature on women's entrepreneurship in the digital space, highlighting the need for supportive ecosystems, policy interventions, funding and digital literacy programmes in fostering a more inclusive and equitable environment for women entrepreneurs to thrive.